Surgical management of choke through oesophagotomy in a buffalo: A case report - Borakhatariya, Devasee; Gadara , A.B. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
Oesophageal disorders are relatively uncommon in large animals. Oesophageal obstruction is the most frequently encountered clinical presentation in bovine and it may be intraluminal or extra luminal (Haven, 1990). Intraluminal obstruction or “choke” is the most common abnormality that usually occurs when foreign objects, large feedstuff, medicated boluses, trichobezoars, or oesophageal granuloma lodge in the lumen of the oesophagus. Oesophageal obstructions in bovine commonly occur at the pharynx, the cranial aspect of the cervical oesophagus, the thoracic inlet, or the base of the heart (Choudhary et al., 2010). Diagnosis of such problem depends on the history of eating particular foodstuff and clinical signs as bloat, tenesmus, retching, and salivation. External palpation may be used to confirm those located in the cervical oesophagus. Various conservative treatments have been described for the management of oesophageal foreign bodies in bovines. Treatments comprise percutaneous external oesophageal massage, passage of a stomach tube, Thygesen’s probang or an inflated endotracheal tube, and endoscopic removal of the foreign bodies (Mahesh et al., 2010). In spite of the good results obtained by these methods, surgical intervention is still necessary if conservative treatment fails and the animal is economically valuable.